Theory of Planned Behavior on Green Marketing Influence to Green Purchase Decision - Hidayat, Taufiq; Sananta, Dinda Putri (Journal of Digital Marketing and Halal Industry, 2024)
This study investigates the correlation between green marketing and consumer buying behaviour, with a specific focus on Garnier Men consumers in Semarang. A total of 162 participants, who were well-acquainted with Garnier Men products and had knowledge of green marketing, were chosen using purposive sampling. The study utilises Structural Equation Modelling (SEM) with AMOS 24.0 software to analyse the data. The key findings suggest that green marketing has a considerable impact on consumer attitudes and subjective norms, but it does not have a direct effect on green purchase decisions. Attitudes, subjective standards, and perceived behavioural control were identified as key factors influencing green purchase behaviour. The report emphasises the necessity for organisations to prioritise these variables instead of exclusively depending on green marketing methods. Furthermore, the study emphasises the significance of providing concise and easily understandable information regarding the environmental effects of products. The research, however perceptive, is constrained to a particular demographic and product line, indicating that future research should encompass a wider array of age groups, professional backgrounds, and product categories in order to improve its generalizability.